PECULIARITIES OF AN ASSOCIATION OF POLYMORPHOUS MARKERS -251 Т>А OF IL-8 GENE AND POLYMORPHISM OF HELICOBACTER PYLORI GENES IN NATIVE AND VISITANT POPULATION OF THE REPUBLIC OF KHAKASSIA - E. S. Ageeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
We researched, polymorphism, of interleukin IL-8 gene at Helicobacter pylori-associated diseases: ulcers and chronic gastritis in native and visitant population of the Republic of Khakassia by the method, of restriction enzyme digest analysis. Prevalence of subtypes VacA+ and CagA+ of Helicobacter pylori was realized, by the method, of polymerase chain reaction. We revealed, the most widespread allelic variants of genes of cytokines among Khakas. The expediency of determination, of population, risk and. protective genotypes of Helicobacter pylori that promote development of ulcer desease in Khakas.